2019
DOI: 10.3390/nu11081943
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Chain Fatty Acid Acetate in Body Weight Control and Insulin Sensitivity

Abstract: The interplay of gut microbiota, host metabolism, and metabolic health has gained increased attention. Gut microbiota may play a regulatory role in gastrointestinal health, substrate metabolism, and peripheral tissues including adipose tissue, skeletal muscle, liver, and pancreas via its metabolites short-chain fatty acids (SCFA). Animal and human data demonstrated that, in particular, acetate beneficially affects host energy and substrate metabolism via secretion of the gut hormones like glucagon-like peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
273
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(287 citation statements)
references
References 205 publications
(278 reference statements)
7
273
0
7
Order By: Relevance
“…The higher acetate concentration can be ascribed to several intestinal bacteria found to be more abundant in GSD gut microbiota, including Akkermansia muciniphila and Bifidobacterium spp., which produce acetate by fermenting acetogenic fibers, and to a lesser extent, protein-derived peptides [44].…”
Section: Discussionmentioning
confidence: 99%
“…The higher acetate concentration can be ascribed to several intestinal bacteria found to be more abundant in GSD gut microbiota, including Akkermansia muciniphila and Bifidobacterium spp., which produce acetate by fermenting acetogenic fibers, and to a lesser extent, protein-derived peptides [44].…”
Section: Discussionmentioning
confidence: 99%
“…Fat cells release leptin in higher concentration by the presence of acetate [223]. In a human study with thirty-four morbidly obese women and men through NMR analysis, increased plasma levels of acetate were found, with a positive correlation with gut Firmicutes, and negatively correlated with HOMA-IR and fasting TG [223,224]. In a study with NAFLD patients, acetate was found increased in circulatory level and fecal level, analyzed by NMR.…”
Section: Acetatementioning
confidence: 93%
“…Firmicutes are positive related to acetate, thus when dysbiosis cause an increase of Firmicutes in obese rats, plasma acetate levels increase, and it is linked to insulin action in morbidly obese individuals through circulating acetate. Fat cells release leptin in higher concentration by the presence of acetate [223]. In a human study with thirty-four morbidly obese women and men through NMR analysis, increased plasma levels of acetate were found, with a positive correlation with gut Firmicutes, and negatively correlated with HOMA-IR and fasting TG [223,224].…”
Section: Acetatementioning
confidence: 98%
See 1 more Smart Citation
“…In humans, previous studies showed influence of gut microbiota in muscle fitness and degradation [13,14]. Symbiotic microbial population residing in humans supply short-chain fatty acids (SCFAs) to the skeletal muscle resulting in improved muscle percentage and fitness, whereas dysbiosis (imbalance in microbiota) results in muscle degradation in host due to increased intestinal permeability and liberation of endotoxin into circulation [14][15][16]. Muscle constitutes about 50-60% of the fish body weight [17] and plays a significant role in the regulation of nutrient metabolism, growth, and inflammation in humans as well as in fish [18][19][20].…”
Section: Introductionmentioning
confidence: 99%